The way to precision medicine in gynecologic cancers: The first case report of an exceptional response to alpelisib in a PIK3CA-mutated endometrial cancer - Passarelli, Anna; Ventriglia, Jole; Pisano, Carmela; Cecere, Sabrina Chiara; Napoli, Marilena Di; Rossetti, Sabrina; Tambaro, Rosa; Tarotto, Luca; Fiore, Francesco; Farolfi, Alberto; Bartoletti, Michele; Pignata, Sandro (Frontiers in Oncology, 2023)
Endometrial cancer (EC) is the most common gynecologic cancer in Europe and its prevalence is increasing. EC includes a biological and clinical heterogeneous group of tumors, usually classified as type I (endometrioid) or type II (non-endometrioid) based on the histopathological characteristics. In 2013, a new molecular classification was proposed by The Cancer Genome Atlas (TCGA) based on the comprehensive molecular profiling of EC. Several molecular somatic alterations have been described in development and progression of EC. Using these molecular features, EC was reclassified into four subgroups: POLE ultra-mutated, MSI hypermutated, copy-number low, and copy-number high that correlate with the prognosis. To this regard, it is widely reported that EC has more frequent mutations in the phosphatidylinositol 3-kinase (PI3K) pathway signaling than any other tumor. PIK3CA is the main significant mutated gene after PTEN alterations. Overall, over 90% of endometrioid tumors have activating PI3K molecular alterations that suggests its critical role in the EC pathogenesis. Thus, the dysregulation of PI3K pathway represents an attractive target in EC treatment. Herein, we report the clinical case of a 51-year-old woman with advanced endometrioid EC with a high expression of hormone receptors and microsatellite stability who having always disease progression after seven lines of systemic treatments including several chemotherapy regimens and hormone therapy. Finally, a comprehensive genomic profiling on tumor tissue was performed, revealing a PIK3CA mutation in exon 20 (H1047R), which was considered targetable. The patient achieved a radiological and clinically meaningful response to a PI3K alpha-selective inhibitor namely alpelisib. These evidences provide the rational for translational strategies of the PI3K inhibition and could support the clinical usefulness of PIK3CA genotyping in advanced EC. To our knowledge, this is the first clinical case of PIK3CA-mutated EC successfully treated with alpelisib.